Effects of fumonisin B1 on performance of juvenile Baltic salmon (Salmo salar) - Carrera Garcia, Erika (2013)
Fumonisin B1 is a mycotoxin produced by fungi of the genus Fusarium that frequently occurs on maize (Zea mays) and feeds containing it. The use of plant-based protein sources in feeds designed for aquaculture has increased due to their low costs compared with fishmeal. This trend has resulted in a global increase in feed formulations contaminated with mycotoxins, producing economical losses in aquaculture industry. The topic also causes concerns because of the potential health consequences that aquaculture products could have on human consumers. FB1 mainly disrupts sphingolipid metabolism and also has immune suppressive effects. Fish mycotoxicosis produces a wide range of symptoms from poor growth rate and weight gain to reproductive, immune, liver and kidney disorders that can lead to mortality. Despite its importance, very little is known about the effects of FB1 in Baltic salmon, Salmo salar. In this study growth performance, feed intake, mortality and liver histopathology of juvenile salmon exposed to FB1 doses 0, 1, 5, 10 or 20 mg/kg feed was evaluated. The hypothesis was that FB1 ingestion would reduce salmon growth, feed intake and would produce liver damage. At the end of the 10-week experiment no differences in the evaluated parameters were found. Species-specific differences in vulnerability because of variations in toxin metabolism could explain the results. However, due to the slow growth of fish during the trial additional research to confirm the results are suggested.